ENGARUH PERCEIVED INFORMATIVENESS KAMPANYE “THE POWER OF CLOTHING”, SIKAP TERHADAP FAST FASHION, DAN SIKAP TERHADAP GREENWASHING TERHADAP PERSEPSI GREEN BRAND UNIQLO - Jessica Inez Indriani, Febronia; Surayya Ulfa, Nurist; Naryoso, Agus (Interaksi Online, 2024)
Currently, brands worldwide are engaging in sustainability campaigns as part of their green marketing strategies. Uniqlo, a leading fast fashion company, has initiated a sustainability campaign titled "The Power of Clothing," which has been disseminated through its official social media channels. However, Uniqlo's transparency index still ranks below its competitors. Additionally, there are several obstacles to the effectiveness of the campaign, such as the emergence of negative consumer attitudes toward fast fashion and skepticism regarding greenwashing. Data was collected through questionnaires distributed to 100 respondents using purposive sampling techniques. The study employs computer-mediated communication theory and cognitive dissonance theory. The research findings from a simple linear regression test indicate that the perceived informativeness of the "The Power of Clothing" campaign (X1) has a significant effect on the perception of Uniqlo as a green brand. The direction coefficient of the regression shows a positive influence of 0.452. Meanwhile, the results of the multiple linear regression test indicate that there is no significant effect of attitudes toward fast fashion and greenwashing on the perception of Uniqlo as a green brand.